Tobacco rattle virus vector: A rapid and transient means of silencing manduca sexta genes by plant mediated RNA interference. - Pavan Kumar (Public Library of Science (PLoS), 2012)
Background RNAi can be achieved in insect herbivores by feeding them host plants stably transformed to express double stranded RNA (dsRNA) of selected midgut-expressed genes. However, the development of stably transformed plants is a slow and laborious process and here we developed a rapid, reliable and transient method. We used viral vectors to produce dsRNA in the host plant Nicotiana attenuata to transiently silence midgut genes of the plant's lepidopteran specialist herbivore, Manduca sexta. To compare the efficacy of longer, undiced dsRNA for insect gene silencing, we silenced N. attenuata's dicer genes (NaDCL1- 4) in all combinations in a plant stably transformed to express dsRNA targeting an insect gene. Methodology/principal findings Stable transgenic N. attenuata plants harboring a 312 bp fragment of MsCYP6B46 in an inverted repeat orientation (ir-CYP6B46) were generated to produce CYP6B46 dsRNA. After consuming these plants, transcripts of CYP6B46 were significantly reduced in M. sexta larval midguts. The same 312 bp cDNA was cloned in an antisense orientation into a TRV vector and Agro-infiltrated into N. attenuata plants. When larvae ingested these plants, similar reductions in CYP6B46 transcripts were observed without reducing transcripts of the most closely related MsCYP6B45. We used this transient method to rapidly silence the expression of two additional midgut-expressed MsCYPs. CYP6B46 transcripts were further reduced in midguts, when the larvae fed on ir-CYP6B46 plants transiently silenced for two combinations of NaDCLs (DCL1/3/4 and DCL2/3/4) and contained higher concentrations of longer, undiced CYP6B46 dsRNA. Conclusions Both stable and transient expression of CYP6B46 dsRNA in host plants provides a specific and robust means of silencing this gene in M. sexta larvae, but the transient system is better suited for high throughput analyses. Transiently silencing NaDCLs in ir-CYP6B46 plants increased the silencing of MsCYP6B46, suggested that insect's RNAi machinery is more efficient with longer lengths of ingested dsRNA.